Andermans schuld?! : [STRIPVERHAAL] - Adriaenssens, Ivan, ....- (Brussel : Vlaams Centrum Schuldbemiddeling)
Deze strip doet nadenken over hoe je met geld omgaat!
Doelgroep: Tieners
Keywords: Geldbeheer -- Jeugd